Կախարդ-հմայք-ջատուկ-վհուկ համանիշային շարքի մասին - Սիլվա Պապիկյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В синонимическом ряду kaxard - hmayk-ĵatuk - vhuk есть семасиологические различия. Эти слова, заимствованные из среднеперсидского языка, вошли в лексический состав армянского языка и употребляются в разных стилях. There are semantic differences in the synonymic series of kaxard - hmayk - ĵatuk - vhuk. These words are loans from the Middle Iranian language. They were assimilated to Armenian vocabulary and are applicable in different styles.
Keywords: Language and Literature